Genesis of the Zhilingtou gold deposit, Zhejiang Province, China: constraints from fluid inclusions and H–O–S–Pb isotope systematics - Liu, Hanlun; Yu, Xiaofei; Duan, Shigang; Sun, Yandong; Wang, Yingchao; Mao, Jingwen (Frontiers in Earth Science, 2025)
The Zhilingtou gold deposit in Zhejiang Province, China, is located in the Qin-Hang metallogenic belt and hosted within Paleoproterozoic Badu Group gneiss. Geologic and isotopic analyses reveal that the gold mineralization is associated with a concealed biotite monzogranite (230 ± 1 Ma) and developed along the contact zone with gneiss. Ore-forming fluids, characterized by moderate—high temperatures (237–376°C) and low salinities (1.90–6.72 wt.% NaCl eqv), originated from a magmatic source and were later diluted by meteoric water, leading to gold precipitation. Pb isotopes indicate a crustal origin for lead, closely related to the Badu Group gneiss. The deposit likely formed in a late Triassic postcollisional extensional setting during the Indosinian orogeny involving the South China and North China blocks, suggesting an intrusion-related gold deposit (IRGD) model with excellent potential for further exploration.